2003
DOI: 10.1063/1.1591187
|View full text |Cite
|
Sign up to set email alerts
|

Complete nondestructive diagnostic of nonneutral plasmas based on the detection of electrostatic modes

Abstract: The detection of electrostatic nonneutral plasma modes in the ATHENA (ApparaTus for High precision Experiment on Neutral Antimatter) experiment [M. Amoretti, C. Amsler, G. Bonomi et al., Nature (London) 419, 456 (2002)] is described. A complete nondestructive diagnostic of the plasma based on a fit to the line shape of the function describing the power transmitted through the plasma around the frequency of the fundamental mode is developed and the experimental results are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 28 publications
1
66
1
Order By: Relevance
“…In order to increase the density of the plasma inside the 3 T solenoid, it can be compressed by employing a rotating wall (RW) electric field [14,15]. A nondestructive plasma diagnostic technique has recently been developed using electrostatic mode analysis [16,17] facilitating realtime monitoring of the plasma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the density of the plasma inside the 3 T solenoid, it can be compressed by employing a rotating wall (RW) electric field [14,15]. A nondestructive plasma diagnostic technique has recently been developed using electrostatic mode analysis [16,17] facilitating realtime monitoring of the plasma.…”
mentioning
confidence: 99%
“…Extensive surveys were made to optimize the performance in terms of frequency, amplitude, sweep, and duration. During the experiments the plasma parameters were monitored using the mode analysis system; in particular, the (1,0) dipole and (2,0) quadrupole frequencies [17] were used to obtain the plasma density, aspect ratio, and length. The positron number was cross-checked by dumping the positrons on a Faraday cup at the end of each measurement.…”
mentioning
confidence: 99%
“…-we used the information we have on the e + plasma shape [13,14] to generate the Pn starting point distributions (in particular, it was found that the e + plasma was approximately a spheroid with radius r p =1 mm and axial half-length z p =16 mm, rotating with a frequency of 300 kHz; i.e. a surface velocity of about 2000 ms −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our model describes the signal induced on an electrode by the coherent oscillations of the dipole mode when an external driving force is applied. In particular we write [16] …”
mentioning
confidence: 99%
“…where m is the positron (or electron) mass [16]. The re- sistance R s characterizes the damping rate of the mode.…”
mentioning
confidence: 99%